2009
DOI: 10.1186/1423-0127-16-60
|View full text |Cite
|
Sign up to set email alerts
|

Activation of estrogen receptor β-dependent nitric oxide signaling mediates the hypotensive effects of estrogen in the rostral ventrolateral medulla of anesthetized rats

Abstract: Background: Apart from their well-known peripheral cardiovascular effects, emerging evidence indicates that estrogen acts as a modulator in the brain to regulate cardiovascular functions. The underlying mechanisms of estrogen in central cardiovascular regulation, however, are poorly understood. The present study investigated the cardiovascular effects of 17β-estradiol (E2β) in the rostral ventrolateral medulla (RVLM), where sympathetic premotor neurons are located, and delineated the engagement of nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 43 publications
3
35
1
Order By: Relevance
“…Although previous studies demonstrated that in the blood vessels, estradiol induces arterial vasodilatation following adverse circulatory conditions such as trauma-hemorrhage (Guo et al, 2005;Shih, 2009;Simoncini et al, 2002), from our results, it seems that neither DPN nor PPT had any effect on either MBP or HR. This could support one proposition (Yu et al, 2007), which suggested that the central vasodepressor effects after activation of ERβ in the rostral ventrolateral medulla (RVLM) is a dose-related manner and that ERα agonist (PPT) did not affect the basal hemodynamic parameters.…”
Section: Discussioncontrasting
confidence: 80%
“…Although previous studies demonstrated that in the blood vessels, estradiol induces arterial vasodilatation following adverse circulatory conditions such as trauma-hemorrhage (Guo et al, 2005;Shih, 2009;Simoncini et al, 2002), from our results, it seems that neither DPN nor PPT had any effect on either MBP or HR. This could support one proposition (Yu et al, 2007), which suggested that the central vasodepressor effects after activation of ERβ in the rostral ventrolateral medulla (RVLM) is a dose-related manner and that ERα agonist (PPT) did not affect the basal hemodynamic parameters.…”
Section: Discussioncontrasting
confidence: 80%
“…In our previous study, the upregulation of sodium hydrogen exchanger-3 (NHE3) expression via ER␤ was found in mouse proximal colon, in parallel with the increase of circulating estrogen levels during pregnancy [34]. Moreover, circulating estrogen-dependent activation has been reported for both reproductive and non-reproductive organs [1,35]. In the present study, ER␤ expression was found at each sampling point irrespective of sex.…”
Section: Discussionsupporting
confidence: 51%
“…For instance, DPN injection at the rostral ventrolateral medulla, an area associated with autonomic cardiovascular control, has been shown to reduce systemic arterial pressure in rats. (103) That ERβ activation can reduce systemic arterial pressure via autonomic influence indicates that additional autonomic cardioprotective mechanisms attributed to E 2 may be mediated through ERβ. Indeed, E 2 -linked cardioprotection has been associated with reduced sympathetic input to the heart and vasculature during ischemia in female rats, resulting in reduced heart rate, mean arterial pressure, arrhythmia frequency, and overall improved ischemic tolerance vs.…”
Section: Introductionmentioning
confidence: 99%